The experience of the breastfeeding/early weaning process by women orientated to breastfeeding: a qualitative study - Raquel Magalhães Rodrigues e Silva; Clarice Marcolino (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
Problem:  The review of literature on breastfeeding/early weaning limits its conditionings on biological aspects, not including the subjectivities of the women who are breastfeeding. Objective: to understand the phenomenon of breastfeeding/early weaning from the discourse of women who experienced it. Method: It is a qualitative approach. The data were collected from a mid-sized private hospital maternity in the City of Belo Horizonte, Minas Gerais, Brazil. We interviewed twelve women who stopped breastfeeding early, using a question guide. The speeches were comprehensively analyzed. According to the speeches, the two categories that emerged were: feelings experienced during breastfeeding and life-world of mothers. Main results: The revealing of speeches showed that women experienced ambivalent feelings in relation to breastfeeding, which may be positive, negative or ambiguous. Also present are the conflicts experienced by the mothers that breastfeeds and works. Conclusions: The tensions generated during the period of lactation have an influence on breastfeeding/weaning.